2020
DOI: 10.1055/a-1083-6580
|View full text |Cite
|
Sign up to set email alerts
|

Femoropatellar Joint Reaction Detected During a 4486 KM Ultramarathon with Mobile MRI

Abstract: Almost nothing is known about the condition of the knee joints of multistage ultra-marathon (MSUM) runner. This is first image-based investigation of the femoropatellar joint (FPJ) using a mobile 1.5T MRI accompanying the MSUM TransEurope Foot-Race (TEFR) 64 stages over 4486 km. Twenty-two (20 male) subjects got a knee MRI-protocol at defined measurement intervals during TEFR: T2*-mapping (FLASH T2*-GRE), TIRM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
1
3
0
Order By: Relevance
“…As animal experiments have shown that ongoing ultra-long load bearing exercises minimize the development of OA in rats 96 and dogs 83 , and as our collective of highly adapted and experienced ultra-runners 105 did not show increased cartilage degeneration, we found significant recovery of T2 values after TEFR (tx), as reported in all three published post-marathon studies with a second follow-up 34,39,40 www.nature.com/scientificreports www.nature.com/scientificreports/ burden does not correspond to increased OA or overuse lesions in the human knee joint when relevant cartilage injuries or malalignments are absent 16,106 . Therefore, despite the problems that have been discussed with overuse injuries in ultra-marathon running [107][108][109][110][111][112][113][114] , MSUMs do not seem to have a negative effect, but rather a favourable influence, on cartilage.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As animal experiments have shown that ongoing ultra-long load bearing exercises minimize the development of OA in rats 96 and dogs 83 , and as our collective of highly adapted and experienced ultra-runners 105 did not show increased cartilage degeneration, we found significant recovery of T2 values after TEFR (tx), as reported in all three published post-marathon studies with a second follow-up 34,39,40 www.nature.com/scientificreports www.nature.com/scientificreports/ burden does not correspond to increased OA or overuse lesions in the human knee joint when relevant cartilage injuries or malalignments are absent 16,106 . Therefore, despite the problems that have been discussed with overuse injuries in ultra-marathon running [107][108][109][110][111][112][113][114] , MSUMs do not seem to have a negative effect, but rather a favourable influence, on cartilage.…”
Section: Discussionsupporting
confidence: 72%
“…The results of this mobile MRI-based field study allow us to refute a relevant negative influence of ultra-long running distances on knee joint cartilage in ultra-marathoners 106 . However, in addition to the factor of running distance, there are other external running-specific characteristics (e.g., competition runners, mountain running with inclines and descents, cross-country running with enhanced multiaxial stress on the knee joints., interval running with partially high running speed, etc.)…”
Section: Discussionmentioning
confidence: 73%
“…Some MRI studies show that even running 4487 km in a multistage UM does not cause permanent negative changes in the knee joint [13,14]. Potential overload injuries during long runs are influenced by a number of individual factors: biochemical, clinical, and anthropometric [15].…”
Section: Knee Overload Injuries In Um Runnersmentioning
confidence: 99%
“…Unfortunately, these studies often focus on one variable or field of study [ 5 - 26 ], particularly cardiac, renal, or psychomotivational functions. Moreover, of these 23 studies, 12 (52%) protocols were conducted on a treadmill [ 5 , 13 , 19 , 27 ], on roads or nontechnical trails [ 6 , 10 , 12 , 18 , 23 , 28 ], on short distances [ 16 ], or in an extreme environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%